ANALYSIS OF THE DEVELOPMENT OF TEACHING METHODS FOR JAPANESE GRAMMAR: A LITERATURE REVIEW STUDY FROM 2000–2025 - Imelda Imelda (International Journal of Teaching and Learning, 2025)
This study examines the development of Japanese grammar teaching methods from 2000 to 2025 through a comprehensive literature review. The main focus of the study is to analyse the paradigm shift in grammar teaching from traditional memorisation-oriented methods to more communicative, contextual, and technology-based methods. This study also discusses the impact of digital technology integration, task-based approaches, blended learning, and the influence of cultural aspects in the Japanese grammar learning process. The results show that adapting teaching methods to student needs and technological developments is essential to improve the effectiveness of bunpō learning. The implications of these findings are expected to serve as a reference for teachers, curriculum developers, and researchers in their efforts to improve and develop relevant and effective bunpō teaching methods in the future.